The Accelerator in Income Analysis: Comment - Hamberg, D. (Quarterly Journal of Economics, 1952)
Journal Article The Accelerator in Income Analysis: Comment Get access D. Hamberg D. Hamberg University of Maryland Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 66, Issue 4, November 1952, Pages 592–596, https://doi.org/10.2307/1882108 Published: 01 November 1952